INCIDENCE AND RISK FACTORS OF LYMPHEDEMA AFTER REGIONAL TREATMENT OF BREAST CANCER - Ghalib, Hawar Hasan Ali; Mohammed, Dara Ahmed; Xaznazdr, Kanar Abubakr; Abdullah, Khalid Mustafa (Journal of Sulaimani Medical College, 2020)
Background Lymphedema is a limb swelling caused by the accumulation of protein- rich fluid in the body tissues secondary to the disturbance of lymphatic drainage. Moreover, the most common risk factor is the regional treatments for breast cancer. Objectives To find out the incidence of lymphedema and the risk factors for development of lymphedema after wide local excision, modified radical mastectomy, axillary lymph node dissection and radiotherapy in patients with breast cancer. Patients and Methods This retrospective study of 288 patients with breast cancer collected from Hiwa Oncology Hospital, Zhianawa Cancer Centre and Breast Diseases Center in Sulaimani Governorate who underwent surgery, chemotherapy and/or radiotherapy during 1st January 2016 to 31st December 2017. All patients had been followed up for duration of (6 - 36) months. Data were collected from each patient. Breast ultrasonography, mammography, fine needle aspiration cytology, and tru-cut biopsy were collected. The arm circumference of the affected-side was measured ten centimeters above and below supracondylar region and the diagnosis of lymphedema was considered if the arm circumference differences were two centimeters or higher. Results The mean ± standard deviation of age (year) was 48.6 ± 10.8 (ranged from 23 to 84) and the majority of the participants were females, with a male to female ratio of (0.03). 74 (25.7%) of the patients were developed lymphedema, 17% of them had lymphedema after surgery, 6.9% of them had lymphedema after radiotherapy and 1.7% of them had lymphedema after both surgery and radiotherapy. Conclusions The types of treatment for breast cancer will affect the occurrence of lymphedema especially if the treatment involves the disturbance of lymphatic drainages and there was a statistically significant association with the lymphedema.
Keywords: Axillary lymph node dissection; Breast cancer; Lymphedema; Modified radical mastectomy; Wide local excision